EVALUATION OF EDUCATION PROGRAM IMPLEMENTATION SCIENCE-BASED MADRASAH ALIYAH - Evi Sopandi; Achmad Siswanto (Akademika : Jurnal Teknologi Pendidikan, 2021)
Abstract:This research aims to evaluate the SAIN-based Madrasah Aliyah (MA) education program in Brebes, Central Java. The education program aims to improve the competence of human resources in improving ability. The evaluation model used in this study is the CIPP model (context, input, process, and product) of the qualitative research approach model introduced by Stufflebeam. The results showed that madrasah sains education program has been running well in accordance with the educational program that has been compiled. However, in the implementation of Madrasah SAIN education, there are still some shortcomings both in the field of funding (low teacher incentives), facilities and infrastructure (there are no adequate laboratories) and about the development of low human resources competencies of teachers.